An Analysis of the Fairness, Sufficiency, and Clarity of Section 71 of the Companies Act 2008 for the Removal of Directors - Shnketa, Isreal (University of the Witwatersrand, Johannesburg, 2024)
The removal of directors in corporate governance is a subject of paramount importance, as it pertains to the dynamic equilibrium of power within a company. This research report delves into the intricate landscape of director removal by shareholders under section 71 of the South African Companies Act.1 Specifically, it scrutinises the contested view that shareholders are not obligated to supply motives for their removal decisions, relying solely on an ordinary resolution. This report examines the implications of the above provision on the delicate balance of power shared between directors and shareholders within the corporate structure. It traverses the historical evolution of director removal laws in South Africa, offering a comprehensive analysis of the legislative framework and its historical context. Furthermore, this report aims to critically assess the recent Miller v Natmed Defence (Pty) Ltd2 case, a landmark judgment, which like the case of Pretorius v Timcke3 challenges the conventional understanding of director removal. While Miller is currently binding only within a specific province, its dissent from the Pretorius case on the requirement for shareholders to provide reasons for director removal sparks debate and calls for further exploration by the higher courts. The findings of this research report aim to contribute to a nuanced understanding of the legal intricacies surrounding director removal and its implications for corporate governance in South Africa. The conclusions drawn shed light on the evolving dynamics of power, underscore the need for legal clarity, and beckon for potential legislative adjustments in pursuit of a balanced and transparent corporate landscape.
A research report submitted in fulfillment of the requirements for the Master of Laws, In the Faculty of Faculty of Commerce, Law and Management, School of Law, University of the Witwatersrand, Johannesburg, 2024
Keywords: UCTD; Director removal; Corporate governance; Section 71 of the Companies Act; Shareholder rights; SDG-17: Partnerships for the goals